Economía popular para una sociedad no capitalista: notas sobre el caso venezolano (Tema Central) - Iturriza López, Reinaldo (2006)
The article examines the initiatives that in the field of popular economics have, since 2004, propelles the Venezuelan state, specifically through the Misión Vuelvan Caras. It describes the progress of the revolutionary process from 1998 up to the beginning of 2006, stressing the argument that the destabilizing strategy of the Venezuelan opposition has been answered from the state and the popular movement with a radicalization of the political process. It is explained, that in this context, there exists the consolidation of an idea-force, which sustains a deep questioning of the development model that reigns in Venezuela, and which has made possible the application of public policies of anti-capitalist orientation.